Impacts and Implications of Asymmetric Climate Policies on Trade and Environment: Evidence From EU - Taşkın, F. Dilvin; Demir, Efe (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This paper critically addresses the need for a unified global climate policy, as opposed to region-specific emission trading systems, with a primary aim to contribute valuable insights to the ongoing discourse. Focused on the aluminum, cement, and iron and steel industries outlined in the EU’s Carbon Border Adjustment Mechanism (CBAM) proposal, our comprehensive analysis using gravity model for trade, centers on testing the validity of the Pollution Haven Hypothesis and Porter Hypothesis. Drawing on data from 10 major EU economies and 19 OECD partners across continents, our study demonstrates that carbon leakage predominantly occurs through trade channels, wherein countries import carbon-intensive products from less regulated nations. Our findings substantiate the Pollution Haven Hypothesis, revealing unintended pollution havens resulting from stringent environmental regulations, leading to carbon leakage through trade or production relocation. In contrast, supporting the Porter Hypothesis, our research underscores how stringent environmental policies can drive innovation within polluting countries, obviating the need for relocation or product imports. By substantiating both hypotheses, our paper advocates for a globally uniform climate policy and emphasizes the potential drawbacks of asymmetrical approaches. The central aim is to contribute to the understanding of how such policies may inadvertently contribute to trade-induced leakage, undermining the positive impact of local systems on a global scale. In light of ambitious climate targets, our study underscores the urgency for synchronized global efforts, reinforcing the call for consistent policies to effectively address the challenges of climate change.